Factors Influencing Pre-School Learners' Enrolment in Kenya - Odindo, Charles O. (JOOUST, 2015)
There has been low pre-school enrolment in Madiany Division, Rarieda sub-County for some time now. Despite the Kenya government's efforts to provide Universal Primary Education, which is in line with Education For All and Millennium Development goals, there has been education wastage through inadequate pre-school enrolment. Using the Lev Vygotsky's socio-cultural and Maslow's hierarchy of needs theoretical perspectives, this study focused on the factors that influence pre-school enrolment in Madiany Division. The study objectives were; to determine the economic factors that influence enrolment of learners in ECDE centres in Madiany Division, to examine the Education Policy factors that influence enrolment at pre¬school level, to identify school based factors that influence pre-school enrolment and to investigate strategies of improving enrolment in ECDE centres in Madiany Division. The study adopted a descriptive survey design that targeted 280 participants who were mainly ECDE teachers in Madiany Division. A sample size of 84 respondents comprising of ECDE teachers were selected using simple random sampling technique. A questionnaire and an interview schedule were used as instruments of data collection, both of which were used on ECDE teachers in Madiany Division. The validity of the instruments was ensured by expert judgment by the university supervisors while the relia6ility of questionnaires was ensured by the split half method, and reliability coefficient of 0. 796 was reported. Descriptive statistics mainly frequencies and percentages were used to analyze the quantitative data which was presented in frequency tables and bar charts while in qualitative data the study used thematic analysis. The study revealed that there were economic factors such as income level of parents, economic activities around the school, number/status of children in a family, parental level of education and socio-economic status of the community influenced pre-school enrolment. The study also found out that policy factors such as entry behavior/school readiness, Free Primary Education policy, language policy, enrolment age, teacher employment policy and teacher pupil ratio influenced pre-school enrolment. There were also school based factors that influenced pre-school enrolment including inadequate sanitation, teaching learning resources, teacher pupil relationship, school distance, teacher turnover, play materials and teacher competence. The study recommends that the Ministry of Education reduces the burden of direct cost of ECDE schooling on parents by increasing and sustaining government allocation to the ECDE sub-sector, improve on assessment and the general infrastructure of the schools.
Keywords: Pre-School Learners; Pre-School; Kenya.